Organisms Diversity & Evolution - Organisms Diversity & Evolution (Springer Nature, 2026)
Organisms Diversity & Evolution (published by the Gesellschaft fuer Biologische Systematik, GfBS) is devoted to furthering our understanding of all aspects of organismal diversity and evolution. Papers addressing evolutionary aspects of the systematics, phylogenetics, morphology and development, taxonomy and biogeography of any group of eukaryotes, recent or fossil, are welcome. Priority is given to papers with a strong evolutionary and/or phylogenetic focus. Manuscripts presenting important methods or tools or addressing key theoretical, methodological, and philosophical principles related to the study of organismal diversity are also welcome. Species descriptions are welcome as parts of a manuscript of broader interest that strive to integrate such taxonomic information with the other areas of interest mentioned above.
FI 0.83
Q3
Keywords: Life Sciences; Evolutionary Biology; Biología evolutiva; Acuerdos transformativos; Transformative agreements; Organismos eucariotas; Filogenética; Biogeografía